Detection of Mycobacterium species destribution in the sputum samples of tuberculosis patients by PCR-RFLP method in Elazig Province - Ağaçayak, Ahmet; Bulut, Yasemin; Seyrek, Adnan (My University, 2007)
The aim of this study was to detect the Mycobacterium species in the sputum samples collected from tuberculosis patients in Elazig province (located in Eastern Anatolia, Turkey), by PCR-RFLP (Polymerase Chain Reaction-Restriction Fragment Length Polymorphism) method. A total of 60 samples from patients (32 male, 28 female) who were diagnosed as tuberculosis by culture positivity at Elazig Tuberculosis Control Dispensary, were included to the study. After DNA extraction and isolation from the samples, gene region encoding for 65 kDa protein of mycobacteria was amplified with specific primers (first step primers: TB1; 5?-GAG ATC GAC TGG AGG ATC C-3? and TB2; 5?-AGC TGC AGC CCA AAG GTG TT-3?, second step primers: TB1 and TB3; 5?-GTG TTG GAC TCC TCG ACG GT-3?) by using seminested PCR method. According to hsp65 gene region amplification, 51 (85%) samples yielded positive results, while nine (15%) samples could not be identified. Of 51 samples, 44 (86.3%) were identified as M.tuberculosis complex, four (7.8%) were M.scrofulaceum, two (3.9%) were M.avium and one (1.9%) was M.intracellulare, in the restriction assay by HaeIII of the PCR products. In order to identify the species of M.tuberculosis complex, gyrB gene region was amplified in those of 44 samples with qpecific primers (MTUB-f; 5?-TCG GAC GCG TAT GCG ATA TC-3? and MTUB-r; 5?-ACA TAC AGT TCG GAC TTG CG-3?), and the PCR products were restricted by RsaI and TaqI enzymes. In this assay, 34 (77.3%), eight (18.2%), one (2.3%) and one (2.3%) of the 44 M.tuberculosis complex samples were detected as M.tuberculosis, M.bovis, M.microti and M.africanum, respectively. Our data indicated that at least seven different Mycobacterium species were the causative agents of tuberculosis in our region. As a result, researching for species distributions of mycobacteria in all of the parts of Turkey by molecular methods and clarifying their resistance patterns against antituberculous drugs are needed for the effective control of tuberculosis.
Elazi? yöresinde tüberkülozlu hastalar?n balgam örneklerinde mikobakteri tür da??l?m?n?n PCR-RFLP yöntemi ile belirlenmesi
Keywords: Mycobacterium spp; PCR-RFLP; Tuberculosis